2009
DOI: 10.1021/es902284c
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Mechanisms of Arsenate during Coprecipitation with Ferrihydrite in Aqueous Solution

Abstract: Dilute arsenate (As(V)) coprecipitation by ferrihydrite was investigated to determine if treatment of acid mine drainage containing dilute As(V) using coprecipitation is feasible. The sorption density obtained at pH 5 and 7 was nearly identical when As(V) was coprecipitated with ferrihydrite, while it was higher at pH 5 when As(V) was adsorbed on the ferrihydrite. The high sorption density of As(V) to ferrihydrite in coprecipitation with 1-h reaction time suggested that coprecipitation occurs via both adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 27 publications
3
55
0
Order By: Relevance
“…Tokoro et al [23] found that arsenate was primarily adsorbed on ferrihydrite as a surface complex when the initial molar ratio of As/Fe was less than 0.4. Otherwise, a ferric arsenate would be formed instead.…”
Section: Introductionmentioning
confidence: 99%
“…Tokoro et al [23] found that arsenate was primarily adsorbed on ferrihydrite as a surface complex when the initial molar ratio of As/Fe was less than 0.4. Otherwise, a ferric arsenate would be formed instead.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrihydrite, a poorly ordered hydrous Fe oxide with a high specific surface area (241-272 m 2 ·g −1 ) and commonly present in low-temperature geochemical environments, is one of the most important minerals in the sequestration of As (Jang et al 2006;Michel et al 2007). Previous studies showed that abiotically synthesized ferrihydrite has a high capacity for As removal via both co-precipitation and adsorption (Bhandari et al 2011;Jia and Demopoulos 2005;Raven et al 1998;Tokoro et al 2010;Zhao et al 2011). Jia and Demopoulos (2005) suggested that almost all As (300 mg/L) was removed by either adsorption or coprecipitation at molar ratio of Fe/As=8 and pH=8.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it was also reported that green rusts and hydrous ferric oxides were effective in arsenic adsorption [25]. The mechanisms of iron-arsenic combination should be surface complexation and surface precipitation [26].…”
Section: Arsenic Removal By Ferrous Addedmentioning
confidence: 98%